Enhanced Human Bone Marrow Mesenchymal Stem Cell Chondrogenic Differentiation on Cold Atmospheric Plasma Modified Cartilage Scaffold. Issue 1723 (19th December 2014) - Zhu, Wei; Keidar, Michael; Zhang, Lijie Grace
ABSTRACT: Articular cartilage is prone to degeneration and possesses extremely poor self-healing capacity due to its low cell density and absence of blood vessels. It has extensively reported tissue engineered scaffold can be a promising approach for cartilage repair. However, there still remains an inherent lack of desirable scaffolds that stimulate cartilage regrowth with appropriate functional properties. Therefore, in this study, we develop a biomimetic cartilage substitute comprising of electrospun polycaprolactone (PCL) with cold atmospheric plasma (CAP) modified cell favorable surface and sustained bioactive factor (bovine serum albumin (BSA) or transforming growth factor beta 1 (TGF-β1)) incorporated microspheres inside for improving stem cell chondrogenesis and cartilage regeneration. Scanning electron microscopy (SEM) analysis showed the drug delivery spheres homogeneously distribution in the fibrous scaffold. Furthermore, CAP treatment renders the scaffold's surface more hydrophilic and results in more specific vitronectin adsorption as illustrated by contact angle and ELISA testing. Our results showed that the CAP treated scaffold can greatly improve growth and chondrogenic differentiation (such as increased glycosaminoglycan (GAG) synthesis) of human bone marrow-derived mesenchymal stem cells (MSCs).